Confluent and Reticulated Papillomatosis of Carteaud and Gougerot in a Young Nepali Male - Bibush Amatya; Rashmi Sharma; MM Aarif Syed; Aasiya Rajbhandari (Nepal Journal of Dermatology, Venereology & Leprology)
Confluent and reticulated papillomatosis of Carteaud and Gougerot is a keratinization disorder with an infective aetiology. Patients present with hyperpigmented papules on the upper trunk and axillae that coalesce centrally and demonstrate reticulation peripherally. Diagnosis is based on clinical findings, characteristic histopathologic changes and response to therapy. We report a case of a young Nepali male who presented with gradual onset of asymptomatic raised dark brown lesions on his neck, trunk and axillae over the course of eight years. The condition was previously misdiagnosed as pityriasis versicolor and had received oral and topical antifungals. The diagnosis was revised to confluent and reticulated papillomatosis based on clinical and histopathological examination. He was subsequently started on oral minocycline 50 mg twice daily and nightly application of topical tretinoin 0.05% gel. There was complete resolution of all his lesions except for residual hyperpigmentation at the end of two months of therapy. There has been no relapse six months from the end of therapy.  This is to our knowledge, the first case of confluent and reticulated papillomatosis reported from Nepal. Oral minocycline and topical tretinoin should be considered first line in the treatment of confluent and reticulated papillomatosis.